PENINGKATAN SPIRITUAL QUOTIENT ANAK USIA 6-7 TAHUN MELALUI METODE FIELD TRIP DI TK AL-ISLAM GENTENG KULON - Ellyana Ilsan Eka Putri; Maula Miftahur Rohmah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Spiritual quotient (SQ) is very important for developed on early childhood, because of this intelligence becomes be soul intelligence, with this intelligence it may help heal and establish themselves in a whole. Field trip is learning activities in nature free that would be fun and can be presented in various forms like game, observation, discussion, adventure, or project as a media this matter. This research in doing at Al-Islam Maron Genteng Banyuwangi on 2018/2019. The subject of study is the group of 25 children, consists of 22 girls and 18 boys. The research is descriptive research with a qualitative approach. According to the research has done, usage method of field trip to increase SQ child has been shown to improve children’s SQ after researchers compare the assessment initial conditions with the after his field trip method.